Illustrated catalogue of type specimens of Volutidae (Gastropoda) in the Malacological Collection of the Museo de La Plata, Argentina - Nuñez, Maria Veronica (2019)
The Malacology Collection of the Museo de La Plata contains more 13,000 lots from various regions of Argentina and other South American countries. The Collection also includes 511 type lots. Among the oldest type specimens are a large series of marine gastropod from Patagonia which were studied by Fernando Lahille in 1895. He was one of the first's naturalists of the Museo de La Plata, and there between 1893 and 1899, he made several studies in zoology. During that time, he described three species and forty varieties of Volutidae. Herein, we compare Lahille's type specimens, label data, number, and specimen information to the original descriptions and illustrations of these taxa. Each taxon has been photographed in multiple views. This historic type material is entirely composed of shells. This work is the first of a series of photographic catalogues of type material from the Malacology Collection of the Invertebrate Division of Museo de La Plata.